Manifestações, perseguição política, vozes do cárcere: uma análise de A pequena prisão, de Igor Mendes. - Soares, Ana Luisa de Castro (2020)
ABSTRACTThe2013 protests now known as Jornadas de Junho , demonstrations that had great popular participation and became a political landmark in Brazil s recent history, were initially focused on protesting the increase ofthe bus farein São Paulo and othe